2020
DOI: 10.1126/sciimmunol.aba0759
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cell control of systemic immunity and immunotherapy response in liver metastasis

Abstract: Patients with cancer with liver metastasis demonstrate significantly worse outcomes than those without liver metastasis when treated with anti–PD-1 immunotherapy. The mechanism of liver metastases–induced reduction in systemic antitumor immunity is unclear. Using a dual-tumor immunocompetent mouse model, we found that the immune response to tumor antigen presence within the liver led to the systemic suppression of antitumor immunity. The immune suppression was antigen specific and associated with the coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
141
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 78 publications
7
141
0
1
Order By: Relevance
“…The possible reason is that after the effective embolization of tumor feeding artery, the tumor cell necrosis is induced significantly in a short time, and the tumor load is also significantly reduced, which is related to the significant reduction of the immunosuppressive effect on the body. It is well recognized that many tumors bear tumor antigens and can induce T-cell cytotoxic responses (22). The release of tumor antigens then led to local microenvironment immune response and a subsequent reduction of Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason is that after the effective embolization of tumor feeding artery, the tumor cell necrosis is induced significantly in a short time, and the tumor load is also significantly reduced, which is related to the significant reduction of the immunosuppressive effect on the body. It is well recognized that many tumors bear tumor antigens and can induce T-cell cytotoxic responses (22). The release of tumor antigens then led to local microenvironment immune response and a subsequent reduction of Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that the liver pre-metastatic niche is characterized by alteration to innate immune composition, including elevated neutrophils, bone marrow-derived myeloid cells, and M2-polarized macrophages [ 40 , 63 ]. Adaptive immune cells, including CD4+ Th17 polarized and T regulatory (Treg) cells, have also been shown to play a functional role in promoting liver metastasis [ 64 , 65 ]. These innate and adaptive immune cell populations support metastasis in part by limiting anti-tumor immunity via active suppression of the cytotoxic T cell response [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…S3B). As a negative control, we saw low chromosomal copy number correlation when comparing MC38 cells to hepatocytes ( 26 ) and immune cells ( 21 ) (Pearson r = 0.05 and r = 0.17, respectively) (fig. S3B).…”
Section: Resultsmentioning
confidence: 95%
“…We next applied XYZeq to a fixed and cryopreserved heterotopic murine tumor model established by intrahepatic injections of a syngeneic colon adenocarcinoma cell line, MC38, into immunocompetent mice. This model mimics tissue-infiltrating features of metastatic cancer and is associated with a relatively well-defined tumor boundary ( 21 , 22 ). MC38 tumor cells also have immunomodulating properties with previous data showing immune cells infiltrating the tumor/tissue interface approximately 10 days after tumor inoculation ( 23 , 24 ).…”
Section: Resultsmentioning
confidence: 99%